Assessing the influence of leadership style, organizational learning and organizational innovation. Issue 5 (3rd July 2017) - Liao, Shu-Hsien; Chen, Chih-Chiang; Hu, Da-Chian; Chung, Yu-Chun; Liu, Chiu-Ling
Abstract : Purpose: Based on literature development, the purpose of this paper is to propose a conceptual framework and the theoretical model in order to examine the influence of leadership, organizational learning (OL), and organizational innovation (OI) in Taiwan's financial and information technology industries. Design/methodology/approach: Structural equation modeling is employed to evaluate the degree of influence each variable has on the others and whether their relationships differ in different industry. This study investigates a selection of firms from the top 100 financial and the top 1, 000 high-technology enterprises in Taiwan in 2012 as the population. A total of 377 valid responses were collected from 2012 to 2013. Findings: The research results indicate that OL acts as a full mediator between leadership and OI. Furthermore, industry type has moderating effect in the proposed research model. Originality/value: Thus, considering appropriate leadership styles through learning to innovate might be a well leadership model to be further considered by different industries in the global countries.